LITERATURE REVIEW OF AUDIT INVESTIGATION ROLE AND WHISTLEBLOWING SYSTEM IN EFFORTS TO FRAUD DISCLOSURE - Amin Makhmuro; Yulida Army Nurcahya (Transpublika Publisher, 2023)
Economic developments have a good impact on society but also lead to the development of acts of fraud committed by some people which can pose a threat to an institution or a country. This shows that something needs to be done to combat this type of fraud. This study aims to determine the role of investigative audits and whistleblowing systems in efforts to disclose fraud. The method in this study uses a qualitative approach and this type of research is included in the literature review. There are several steps taken by researchers during the research process, such as selecting data, presenting data, and drawing conclusions. The results of the study show that investigative audits and whistleblowing systems have an important role in efforts to identify and disclose fraud.